2016
DOI: 10.1177/1541204016629721
|View full text |Cite
|
Sign up to set email alerts
|

Handgun Carrying Among Youth in the United States

Abstract: Despite a wealth of research finding that adolescents who carry handguns are involved in risky behaviors, there has been little exploration into the heterogeneity of this behavior. Using a pooled sample of 12- to 17-year-olds from the National Study on Drug Use and Health who report past-year handgun carrying ( N = 7,872), this study identified four subgroups of handgun carriers: low risk ( n = 3,831; 47.93%), alcohol and marijuana users ( n = 1,591; 20.16%), fighters ( n = 1,430; 19.40%), and severe externali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…These findings corroborate other correlates found in previous studies (Muula, Rudatsikira, & Siziya, 2008;Vaughn, DeLisi, Salas-Wright, & Maynard, 2014;Vaughn, Perron, Abdon, Olate, & Wu, 2012;Wilkinson & Fagan, 2001;Wintemute, 2015). However, within this externalizing behavior spectrum we found some evidence of differential correlates by race/ethnicity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings corroborate other correlates found in previous studies (Muula, Rudatsikira, & Siziya, 2008;Vaughn, DeLisi, Salas-Wright, & Maynard, 2014;Vaughn, Perron, Abdon, Olate, & Wu, 2012;Wilkinson & Fagan, 2001;Wintemute, 2015). However, within this externalizing behavior spectrum we found some evidence of differential correlates by race/ethnicity.…”
Section: Discussionsupporting
confidence: 93%
“…These include several externalizing spectrum behaviors such as alcohol, marijuana or other drug use, selling drugs, aggression, fighting, and gang affiliation and peer misbehavior (Braga, 2012;;Kulig, Valentine, Griffith, & Ruthazer, 1998;Lizotte, Krohn, Howell, Tobin, & Howard, 2000;;Vaughn, Perron, Abdon, Olate, & Wu, 2012). The co-occurrence of handgun carrying and externalizing behaviors is consistent with several general theoretical explanations that emphasize deficits in impulse control Gottfredson & Hirschi, 1990;Moffitt, 1993).…”
Section: Introductionmentioning
confidence: 52%
“…Given the lethality of interpersonal disputes when handguns are present (Braga, 2012; Caudill & Trulson, 2016; DeLisi, Piquero, & Cardwell, 2016; Farrington, Loeber, Stallings, & Homish, 2012; Reich, Culross, & Behrman, 2002) coupled with the diminished maturation of executive decision-making common in young people, handgun carrying among adolescents is a serious public health and policy concern (Barry, McGinty, Vernick, & Webster, 2015; Blum, 2001; Braga, 2012; Fowler, Dahlberg, Haileyesus, & Annest, 2015; Kleck, 2015; Muula, Rudatsikira, & Siziya, 2008; O’Toole & Fondacaro, 2017; Siegel et al, 2014; Welsh, Braga, & Sullivan, 2014; Wintemute, 2015a, 2015b). While it is well established that male adolescents are more likely to carry handguns (Vaughn, Perron, Abdon, Olate, & Wu, 2012) and engage in antisocial behavior generally (Eme, 2010), relatively less is known regarding the prevalence and correlates of handgun carrying among female adolescents. This is an important oversight as girls who carry handguns may also be at increased risk for a host of other developmental problems besides serious delinquency, such as early pregnancy and motherhood, that may serve to increase the probability for intergenerational transmission of problem behaviors (Loughran, Reid, Collins, & Mulvey, 2016).…”
mentioning
confidence: 99%
“…One study similar in terms of the analytic methods used found four subgroups: a high-risk group, a group characterized by alcohol and marijuana use, a group characterized by aggressive behaviors, and a low-risk group. 98 However, the previous study did not examine psychological distress or peer victimization, which are both highly relevant when considering suicide as a potential outcome of handgun access.…”
Section: Subpopulations Of Handgun-carrying Youth and Suicide Riskmentioning
confidence: 99%
“…However, it is important to note that youth who carry handguns are not a homogenous group. One study identified four subtypes of youth who carry handguns: one with high risk of substance, one with elevated risk of violence, one with high risk of both substance use and violence, and a low risk group 98. This perspective of understanding the coexistence of multiple risk factors is useful in several contexts, including suicide…”
mentioning
confidence: 99%